2015
DOI: 10.1124/jpet.115.229690
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Allosteric Insulin Receptor-Activating Antibody Reduces Hyperglycemia without Hypoglycemia in Diabetic Cynomolgus Monkeys

Abstract: XMetA is a fully human, allosteric monoclonal antibody that binds the insulin receptor with high affinity and mimics the glucoregulatory, but not the mitogenic, actions of insulin. Here we evaluated the efficacy of both single and repeat s.c. administrations of XMetA in reducing hyperglycemia in obese cynomolgus monkeys with naturally developed type 2 diabetes, a model that shares many features of human diabetes. The data show that a single s.c. administration of XMetA at dose levels ranging from 1.5 to 10 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…However, such bivalent antibodies can also bind and activate WT human INSR (14), and naturally occurring polyclonal anti-INSR antibodies induce hypoglycaemia at low titres, and extreme insulin resistance at high titres in humans (19). On the other hand, monoclonal human anti-INSR antibodies have been suggested as a therapeutic strategy in common forms of diabetes, without evaluation of effects on receptor expression (9)(10)(11)(12).…”
Section: Antibody Treatment Down-regulates Wild-type Human Insr Exprementioning
confidence: 99%
See 2 more Smart Citations
“…However, such bivalent antibodies can also bind and activate WT human INSR (14), and naturally occurring polyclonal anti-INSR antibodies induce hypoglycaemia at low titres, and extreme insulin resistance at high titres in humans (19). On the other hand, monoclonal human anti-INSR antibodies have been suggested as a therapeutic strategy in common forms of diabetes, without evaluation of effects on receptor expression (9)(10)(11)(12).…”
Section: Antibody Treatment Down-regulates Wild-type Human Insr Exprementioning
confidence: 99%
“…With therapeutic humanised monoclonal antibodies now well established as treatments both for cancer and non-cancer indications (7), interest in biological therapies targeting the INSR has recently rekindled. Inhibitory INSR antibodies are now in Phase 1 human trials(8) while stimulatory antibodies have been shown to ameliorate diabetes in rodents(9-11) and primates (12). Given the high clinical need in recessive insulin receptoropathy, we previously assessed the effect of monoclonal anti-INSR antibodies(13-17) on a series of disease-causing mutant INSRs in cell culture models, corroborating and extending prior findings by demonstrating an action of antibodies against a panel of mutant receptors (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In diet‐induced obese mice, XMetA normalised fasting glucose, corrected glucose tolerance and improved non‐HDL cholesterol with no weight gain or hypoglycaemia . Similar results were found recently in a study in diabetic cynomolgus monkeys …”
Section: Pharmacotherapy For Insulin Resistance Under Developmentmentioning
confidence: 99%
“…Interest in biological therapies targeting the INSR has recently rekindled, with inhibitory antibodies in Phase 1 human trials [11] and stimulatory antibodies shown to ameliorate diabetes in rodents [12][13][14] and primates [15]. Given the high clinical need in recessive insulin receptoropathy, we assessed the effect of monoclonal anti-INSR antibodies [16][17][18][19][20] on a series of disease-causing mutant INSRs.…”
Section: Introductionmentioning
confidence: 99%